Self-help digital mental health intervention in improving burnout and mental health outcomes among healthcare workers: a narrative review - Aye, Lwin M.; Tan, Min M.; Schaefer, Alexandre; Thurairajasingam, Sivakumar; Geldsetzer, Pascal; Soon, Lay K.; Reininghaus, Ulrich; Bärnighausen, Till; Su, Tin T. (Digital health, 2024)
Background - Healthcare workers face burnout from high job demands and prolonged working conditions. While mental health services are available, barriers to access persist. Evidence suggests digital platforms can enhance accessibility. However, there is a lack of systematic reviews on the effectiveness of digital mental health interventions (DMHIs) for healthcare professionals. This review aims to synthesize evidence on DMHIs’ effectiveness in reducing burnout, their acceptability by users, and implementation lessons learned. - Method - This Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA)-guided review included 12 RCTs on DMHIs for healthcare professionals, published before 31 May 2024. The primary focus was on burnout, with secondary outcomes related to mental health and occupation. Quality appraisal used Cochrane risk of bias tools. A narrative synthesis explored DMHIs’ effectiveness, acceptability, utilization, and implementation lessons. - Results - Significant improvements in mental health outcomes were observed in 10 out of 16 RCTs. Burnout and its constructs showed significant improvement in five RCTs. Studies that measured the acceptability of the interventions reported good acceptability. Factors such as attrition, intervention design and duration, cultural sensitivities, flexibility and ease of use, and support availability were identified as key implementation considerations. - Conclusions - Web-based DMHIs positively impact burnout, mental health, and occupational outcomes among healthcare professionals, as shown in most RCTs. Future research should enhance DMHIs’ effectiveness and acceptability by addressing identified factors. Increasing awareness of DMHIs’ benefits will foster acceptance and positive attitudes. Lessons indicate that improving user engagement and effectiveness requires a multifaceted approach.